Rhizomic Rap: Representation, Identity and Hip-Hop on Moccasin Flats - Burrows, Brendan (Université d'Ottawa / University of Ottawa, 2012)
With the rise of First Nations owned and created television content at the turn of the century, came a demand to see an accurate representation of Aboriginality that could look at Aboriginals as both here and modern. From 2003-2006, the first Aboriginal made and produced television series entitled Moccasin Flats, I argue, used modern day hip-hop discourse to both engage and dissect a host of complex issues facing modern day urban Aboriginal society. This research project mobilizes multiple methodologies; including: 1.) Eco’s code and sign function semiotic analysis, which operates to identify various hip-hop codes in the text; 2.)Hall’s method of articulation to look at how meaning is fixed in the discourse surrounding the show; and finally 3) Deleuze’s rhizomic approach to identity to see how the shows main characters are constructed in a way to highlight the paradoxical and undercut certain flirtations with essentialization. This three-tiered methodological process paints a picture of a new complex use of discourse to accentuate different facets of aboriginality that had previously been the sole product of dominant hegemonic institutions which relied on racist stereotypes. By dissecting how identity is formed on Moccasin Flats, I will show how aboriginal filmmakers construct a self-reflexive space where the character is perpetually in the process of ‘becoming’ and identity is always a site of negotiation.